Integration of Ignatian values in the development of algebraic thinking via utilization of quasi-variables: A lesson study - Marian Grace Veloso; Lucio Landanganon; Raquel Lamanilao; Levi Elipane (Institute of Advanced Engineering and Science, 2021)
This paper reflects on the outcome of lesson study in teaching the concept of algebraic equations utilizing quasi-variables. It also concurrently examines the integration of Ignatian values and social issues in learning the said concept. This study aimed to establish a culture of planning, collaboration, and reflection in developing the understanding and relevance of mathematical concepts in grade school through lesson study. The study showed how the process of lesson study was done given the following phases: planning phase, implementation phase, and post-lesson reflection and discussion phase. Emphasis on the planning phase was given on the details of the lesson design which aimed to integrate Ignatian values in the discussion while developing algebraic thinking from quasi-variable thinking delivered in the implementation phase. Findings highlighted on three statements: i) Collaborative lesson planning nurtures a deeper sense of scholarship and collegiality; ii) Building algebraic thinking from quasi-variable (arithmetic) thinking is a viable strategy for understanding the concept of algebraic equation; and iii) Looking into the “big picture” and responding to relevant social issues could strengthen meaning - integration of Ignatian values. Strong collaboration and communication among teachers in creating detailed lesson design enabled more meaningful learning among pupils. Research revealed the significant role of lesson study in creating meaningful strategies and activities which provided efficient structure in developing a chosen lesson topic. It does not only focus on the nature of the topic but also include making meaningful connections to the real world and integrate values.